2004
DOI: 10.1002/lt.20059
|View full text |Cite
|
Sign up to set email alerts
|

Altered hematologic profiles following donor right hepatectomy and implications for perioperative analgesic management

Abstract: Living liver donors for adult liver transplant recipients undergo extensive liver resection. Partial donor hepatectomies may alter postoperative drug metabolism and hemostasis; thus, the risks and the benefits of pain management for this unique patient population may need to be reassessed. The safety and efficacy of combined epidural analgesia and field infiltration in our initial living liver donor group are presented. A thoracic epidural catheter was placed before general anesthesia in 2 female and 6 male do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 24 publications
(40 reference statements)
1
53
0
1
Order By: Relevance
“…[14][15] However, unwanted complications and the possibility of a labor-intensive and non-functioning epidural catheter make epidural analgesia not an ideal analgesic method for hepatectomy. Large hepatectomy can lead to postoperative coagulopathy, 16 which was confirmed in our study. Recently, epidural analgesia has been suggested to be an independent risk factor for AKI after hepatectomy.…”
Section: Baseline Informationsupporting
confidence: 84%
“…[14][15] However, unwanted complications and the possibility of a labor-intensive and non-functioning epidural catheter make epidural analgesia not an ideal analgesic method for hepatectomy. Large hepatectomy can lead to postoperative coagulopathy, 16 which was confirmed in our study. Recently, epidural analgesia has been suggested to be an independent risk factor for AKI after hepatectomy.…”
Section: Baseline Informationsupporting
confidence: 84%
“…10,14,[33][34] Others have raised concern about the safety of this analgesic modality, particularly when employed for liver resections, which harbor an inherent risk of coagulopathy and hepatotoxicity. [35][36][37] These uncertainties are further compounded by a paucity of randomized trials examining the efficacy of epidural analgesia in upper abdominal operations specifically, particularly in terms of pancreatic operations. Although a frequently cited study-reported by Rigg et al in 2002 16 -did include 35 pancreatic operations (of 915 total), no pancreatic morbidity endpoints were evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…However, administration of morphine is associated with various side-effects [15]. In addition, unexpected sensitivity to systemic opioid has been observed after hepatic resection, perhaps as a result of altered drug metabolism [16]. The plasma concentration of morphine and sedation score were higher in patients after liver resection compared with colonic resection, and this was correlated with the amount of liver resected [17].…”
Section: Discussionmentioning
confidence: 99%